Electronic Structure and Momentum Density of BaO and BaS - R. Kumar; B. K. Sharma; G. Sharma (Advances in Condensed Matter Physics)
The electronic structure and electron momentum density distribution in BaO and BaS are presented using Compton spectroscopy. The first-ever Compton profile measurements on polycrystalline BaO and BaS were performed using 59.54 keV gamma-rays. To interpret the experimental data, we have computed the theoretical Compton profiles of BaO and BaS using the linear combination of atomic orbitals method. In the present computation, the correlation scheme proposed by Perdew-Burke-Ernzerhof and the exchange scheme of Becke were considered. The hybrid B3PW and Hartree-Fock based profiles were also computed for both compounds. The ionic configurations are performed to estimate the charge transfer on compound formation, and the present study suggests charge transfer from Ba to O and S atoms. On the basis of equal-valence-electron-density profiles, it is found that BaO is more ionic as compared to BaS.